Polymerized β-Cyclodextrin-Based Injectable Hydrogel for Sustained Release of 5-Fluorouracil/Methotrexate Mixture in Breast Cancer Management: In Vitro and In Vivo Analytical Validations - Saud Almawash; Mohamed A. El Hamd; Shaaban K. Osman (MDPI AG, 2022)
An inclusion complexation, between polymerized β-cyclodextrin and cholesterol end-capping branched polyethylene glycol, was utilized for constructing a self-assembled hydrogel. The physicochemical properties, the in vitro release profiles of 5-Fluorouracil/methotrexate (anticancer drugs), and the surface morphology of the resulting hydrogel were studied. Moreover, in vivo studies were carried out on female rats bearing breast cancer. The results revealed that the prepared systems were white in color, rubbery, and homogenous. The in vitro release studies showed an efficient ability of the modified system for drug loading and release in a sustained release manner for 14 days. The surface morphology was spongy porous. Moreover, the tumors' healing was indicated from the analysis of tumor volume, plasma tumor markers, and histopathological analysis, compared to the controlled rats. The pharmacokinetic parameters appeared significant differences (p < 0.05) in the Cmax and Tmax of the medicated hydrogel samples, as compared with sole or combined saline-injected samples. The whole AUC of each drug in the medicated hydrogel samples was five-fold more than the mixture administrated in PBS. In conclusion, the proposed work delivered a hydrogel system that has a convenient ability for localized sustained release of breast cancer management.